Readiness of Class Teachers in Implementing Artificial Intelligence-Based Learning at SD Negeri 08 Panyabungan - Arafatul Soraya; Namiroh Lubis (Lembaga Yasin AlSys, 2026)
The development of Artificial Intelligence (AI) in education requires teachers to demonstrate digital readiness to support more effective, personalized, and interactive learning. However, AI-based learning at SD Negeri 08 Panyabungan remains limited, indicating the need for further investigation into teachers’ preparedness and implementation practices. This study aims to examine teachers’ understanding and readiness for AI, analyze its application in classroom learning, and identify the supporting and inhibiting factors affecting AI implementation at SD Negeri 08 Panyabungan. A qualitative approach was employed, with data obtained from the principal, teachers, students, and relevant documents. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman model. Data validity was ensured through triangulation of sources, techniques, and time. The findings show that teachers possess an initial understanding of AI, but their readiness and classroom implementation remain limited and are still developing. AI use is generally indirect and limited to simple digital media rather than fully integrated AI-based learning practices. Key inhibiting factors include limited facilities, unstable internet access, and insufficient teacher training, while the existing use of digital media provides an initial foundation for future development. This study concludes that SD Negeri 08 Panyabungan is still in the early transition stage toward AI-based learning. The study contributes to the discourse on digital transformation in elementary education by highlighting the need for systematic teacher training, adequate infrastructure, and institutional support to strengthen teachers’ readiness for responsible and effective AI integration in classroom learning.